2017
DOI: 10.1039/c7cy00960g
|View full text |Cite
|
Sign up to set email alerts
|

Facile fabrication of a CoO/g-C3N4p–n heterojunction with enhanced photocatalytic activity and stability for tetracycline degradation under visible light

Abstract: The CoO/g-C3N4 p–n heterojunction photocatalysts exhibit enhanced photocatalytic activity and stability under visible light.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 247 publications
(85 citation statements)
references
References 45 publications
5
76
0
Order By: Relevance
“…In spite of the visible-light activity of g-CN close to the blue spectral region, the use of pure g-CN is restricted by rapid photo-generated charge recombination, small surface area, due to the characteristics two-dimensional layered structure [ 22 , 23 ]. In order to minimize the rapid charge recombination and harness the positive features of g-CN, modifications like doping with metal and non-metals and compositing with other co-catalyst have been tried, and these kinds of material engineering have improved the photocatalytic activity of the material to a certain extent, in different applications [ 24 , 25 , 26 ]. Particularly, compositing n-type g-CN with different p-type semiconducting materials like BiOCl, CuS, and SnS 2 has been tried, and it was reported that the resultant p-n heterojunction facilitated the spatial charge separation and consequently resulted in the reduction of charge recombination, which was eventually manifested as the enhancement of photocatalytic efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the visible-light activity of g-CN close to the blue spectral region, the use of pure g-CN is restricted by rapid photo-generated charge recombination, small surface area, due to the characteristics two-dimensional layered structure [ 22 , 23 ]. In order to minimize the rapid charge recombination and harness the positive features of g-CN, modifications like doping with metal and non-metals and compositing with other co-catalyst have been tried, and these kinds of material engineering have improved the photocatalytic activity of the material to a certain extent, in different applications [ 24 , 25 , 26 ]. Particularly, compositing n-type g-CN with different p-type semiconducting materials like BiOCl, CuS, and SnS 2 has been tried, and it was reported that the resultant p-n heterojunction facilitated the spatial charge separation and consequently resulted in the reduction of charge recombination, which was eventually manifested as the enhancement of photocatalytic efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Other g-C 3 N 4 nanocomposites were investigated with a range of materials and morphologies [39,82,91,, to access different charge transfer mechanisms between g-C 3 N 4 and the other components. These include a g-C 3 N 4 -based type II heterojunction [103], g-C 3 N 4 -based p-n heterojunction [91,129], g-C 3 N 4 -based Z-scheme heterojunction [113,130], g-C 3 N 4 /metal heterojunction [100,102], and a g-C 3 N 4 /carbon heterojunction [131]. The design of g-C 3 N 4 heterojunction photocatalysts is an attractive strategy to tune the electronic structure and redox potentials for visible-light absorption photocatalytic H 2 generation.…”
Section: H 2 Evolutionmentioning
confidence: 99%
“…As a result, the p-n heterojunction leads to the formation of positively and negatively charged regions in n-ZnO and p-CuCrO 2 , respectively. This internal electric field improves the separation of photo-generated charge carriers [66]. Under the light irradiation, photo-excited holes in valance band of ZnO can now migrate to valence band of CuCrO 2 .…”
Section: Photocatalytic Properties Of Zno-cucromentioning
confidence: 99%